Data Management and Data Modeling: CharcoalEats - Verma, Vansh (ATLAS SkillTech University, 2025)
The global food technology industry is at the peak of revolution with the rise in demand for sustainable and healthy food choices, coupled with advancements in digital technology. From food processing to its distribution and retailing, every part of the continuum is now looking towards technological advancements to better efficiency, reduce waste, and also meet the rising demands for convenience and personalization.
Project Report on Data Management and Data Modeling: CharcoalEats (2023-2025) Under the Guidance of Prof. Shweta Loonkar
Keywords: food technology; sustainable; healthy food choices; digital technology; food processing; retailing; technological advancements